2020
DOI: 10.1093/braincomms/fcaa145
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of fatty acid binding protein 4 in the pathophysiology of autism spectrum disorder

Abstract: Autism spectrum disorder is a neurodevelopmental disorder characterized by difficulties in social communication and interaction, as well as repetitive and characteristic patterns of behavior. Although the pathogenesis of autism spectrum disorder is unknown, being overweight or obesity during infancy and low weight at birth are known as risks, suggesting a metabolic aspect. In this study, we investigated adipose tissue development as a pathophysiological factor of autism spectrum disorder by examining the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…M et al, recently have demonstrated the downregulation of fatty acid-binding protein 4 (FAB4) in preschool ASD children which was further supported by gene sequencing analysis and mice models knockout for FAB4 gene which showed Autism-like symptoms, suggesting an adipose-brain axis in ASD; they have also proposed FAB4 as a convenient biomarker in ASD. 46 Although we did not assess other inflammatory cytokines along with CTRP1 to test whether there is a correlation between them in ASD children participating in our study, it could be proposed that other inflammatory cytokines might be dysregulated in the ASD group, which needs further evaluations.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…M et al, recently have demonstrated the downregulation of fatty acid-binding protein 4 (FAB4) in preschool ASD children which was further supported by gene sequencing analysis and mice models knockout for FAB4 gene which showed Autism-like symptoms, suggesting an adipose-brain axis in ASD; they have also proposed FAB4 as a convenient biomarker in ASD. 46 Although we did not assess other inflammatory cytokines along with CTRP1 to test whether there is a correlation between them in ASD children participating in our study, it could be proposed that other inflammatory cytokines might be dysregulated in the ASD group, which needs further evaluations.…”
Section: Discussionmentioning
confidence: 86%
“… 87 , 88 In line with previous studies demonstrating the dysregulation of adipokines in ASD patients, our data also indicate that there might be an imbalance of adipokines in ASD children even in the absence of any identifiable metabolic or inflammatory diseases. 44 - 46 , 89 Regarding the high incidence of obesity due to different reasons such as sedimentary life, certain medications, or much desire for food, it has been proposed that ASD children are predisposed to metabolic diseases or dyslipidemia, resulting in aggravation of their inflammatory profile and worsening their symptoms. 90 , 91 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating FABP4 concentration is known as a biomarker for several disorders; increased circulating FABP4 concentrations are associated with the increased risk of various diseases, such as atherosclerosis [7,8], insulin resistance [9], type 2 diabetes [10], hypertension [9,11], dyslipidemia [9,12], cardiovascular diseases [13,14], and cancer [15]. Notably, it has been also recently reported to be a potential biomarker for autism spectrum disorder in children [16]. Thus, circulating FABP4 concentration is increasingly useful as a biomarker of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We have continued to publish papers on a wide range of conditions from neurodevelopmental disorders to neurodegeneration and studies ranging from fundamental neurobiology to diagnostic tools and results of clinical trials (see e.g. Landles et al , 2020 ; Luz et al , 2020 ; Maekawa et al , 2020 ; Ugalde et al , 2020 ; Van Damme et al , 2020 ). We have also published a few timely papers on the neurological and cognitive effects of COVID-19 ( Lleó and Alcolea, 2020 ; Ritchie et al , 2020 ; Woo et al , 2020 ).…”
mentioning
confidence: 99%